Strategi Penulisan Ekspositoris dengan Pendekatan Reflektif dalam Produksi Film Dokumenter “2000 Untuk Parkir : Fenomena Juru Parkir Liar di Jatinangor” - Gilang Rian Syahputra; Iwan Koswara; Jimi Narotama Mahameruaji (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
This study examines the strategy of writing an expository narrative using a reflective approach in the production of the documentary film "2000 Untuk Parkir: Fenomena Juru Parkir Liar di Jatinangor" Using descriptive qualitative methods through participant observation, in-depth interviews, and data triangulation, this 15-minute film presents a three-act plot that integrates empirical facts (such as a daily income of Rp50,000 from a Rp2,000 per vehicle rate) with the filmmaker's critical reflections on the dynamics of the informal economy and urbanization in educational areas. Results of an effectiveness test on 20 student respondents showed an 85% comprehension rate and a 90% increase in critical awareness, demonstrating the superiority of this hybrid approach in building empathy without excessive subjectivity. The discussion confirms the strategy's contribution to the discourse of Indonesian documentary production, with implications for advocacy for inclusive parking policies.